1994
DOI: 10.1210/en.134.2.906
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-dependent selection of brown adipocyte cell lines

Abstract: A transgenic mouse carrying a simian virus-40 T-antigen gene under control of a mouse urinary protein promoter induced the formation of a brown fat tumor. In tissue culture, these tumor cells expressed the brown fat-specific mitochondrial uncoupling protein (Ucp) gene when stimulated by norepinephrine. To develop cell lines for the analysis of Ucp expression, we investigated growth conditions that would maintain expression. We found that the addition of 10(-7)-10(-6) M norepinephrine was critical for establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…51,[85][86][87][88] Early in vitro work from the labs of Kozak and Nedergaard suggested that norepinephrine triggers BA proliferation via ADRB1. [88][89][90][91] These data are in agreement with the fact that ADRB1 are present in BA progenitors, whereas ADRB3 is a marker of the differentiated state. 91 Recently, we reported that knockout of ADRB1 abrogates cold-induced iBAT hyperplasia.…”
Section: Cellular Plasticity In Ibatsupporting
confidence: 79%
“…51,[85][86][87][88] Early in vitro work from the labs of Kozak and Nedergaard suggested that norepinephrine triggers BA proliferation via ADRB1. [88][89][90][91] These data are in agreement with the fact that ADRB1 are present in BA progenitors, whereas ADRB3 is a marker of the differentiated state. 91 Recently, we reported that knockout of ADRB1 abrogates cold-induced iBAT hyperplasia.…”
Section: Cellular Plasticity In Ibatsupporting
confidence: 79%
“…The absence of an accumulation of mitochondria (unpublished observations, X.X. Koza and L.P. Kozak) indicates that expression of Ucp is not sufficient to stimulate mitochondriogenesis, a conclusion reached independently from our analysis of brown adipocyte cell lines (27). Since the aP2 gene is one of the late stage markers of adipocyte differentiation program (28), it is possible that the adipocyte derivatives originate from white preadipocytes.…”
Section: Discussionmentioning
confidence: 70%
“…Markers of macrophages [F4/80 (emr1), scya4, cd11␤, and cd45 (ptprc)], endothelial cells [vegfr (flk1), vegfr2 (kdr), cd46 (mcp), and von Willebrand], and multipotent mesenchymal progenitors (cd34, connexin 43, sox2, and smad4) indicated that age-related shifts in abundance of these cell types in preadipocyte cultures did not account for our results. Brown fat preadipocytes are not present in epididymal cultures, since uncoupling protein 1 is not evident in these cultures after treatment with isoproterenol but is observed in interscapular preadipocyte positive controls (36,41). To induce differentiation, confluent preadipocyte cultures were exposed to a serum-free differentiation-inducing medium (DM) containing 5 g/ml insulin, 10 g/ml transferrin, and 200 pM triiodothyronine in 1:1 DMEM-Ham's F-12 (20).…”
Section: Methodsmentioning
confidence: 99%